A SUPPORT OF THE HUSBAND DURING THE PROCESS OF LABOR AND THE PUERPERIUM IN KUPANG DISTRICT - MARETA BAKALE BAKOIL (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Husband's support during pregnancy, childbirth and the puerperium is needed by both mother and baby. Husband's support makes mothers less stressed, needs are met, mothers feel comfortable emotionally. The purpose study was to determine the husband's support during labor and childbirth. The research method is qualitative exploration with a phenomenological approach. The research was conducted in Oelbiteno Village with the informants were 10 husbands of mothers who gave birth. Data collection by direct interview and via telephone. Data processing and analysis techniques are interpretative phenomenological analysis with content analysis. Results showed husband's support for his wife during childbirth is physical support (massaging the wife's back, feeding and drinking); emotional (feeling what the wife is facing, helping her during childbirth); informational (information about nutritious food); advocacy (planning a safe labor for the wife, preparing clothes for mothers and babies, KTP, KK, JKN). Husband's support during the puerperium period is physical support (caring for the baby, delivering the wife and control baby); emotional (encouraging to provide exclusive breastfeeding); informational (information about wife and child health, nutritious food); advocacy (planning family planning programs).